Reception theory: philosophical hermeneutics, literary theory, and biblical interpretation - Parris, David (1999)
The goal of this thesis is to explore the possibility of applying Hans Robert Jauss' hermeneutic of reception theory to biblical interpretation. The traditional methods employed in biblical interpretation involve a two-way dialogue between the text and the reader. Reception theory expands this into a three-way dialogue, with the third partner being the history of the text's interpretation and application. This third partner has been ignored by biblical interpreters but recently the need to include this has gained some attention. In the first part of the thesis, the work of Hans-Georg Gadamer will be examined in order to provide the philosophical hermeneutical framework for reception theory and its significance for biblical studies. In the second part, this framework will be fleshed out by Hans Robert Jauss' conception of reception theory. Jauss not only builds upon Gadamer's work but his literary hermeneutic provides a model which is applicable to the biblical text and its tradition of interpretation. In the final part, the parable of the Wedding Feast in Matthew 22:1-14 and its Wirkungsgeschichte will be considered as a case study.